Optimasi Minimum Pola Baju Khas Kain Tenun Sarung Samarinda Menggunakan Algoritma Greedy - Hani Subakti; Windu Gata (STMIK AKBA, 2021)
Nowadays, the typical clothes of the Samarinda sarong woven cloth have become a secondary requirement in the daily activities of the people in Samarinda City. In making the typical woven cloth, the sarong of Samarinda requires a sufficient area of the woven cloth to attach it to the pattern of clothes of various sizes. This research requires an appropriate method in measuring the area of woven fabric required for the installation of clothing patterns of various sizes, namely by using the greedy algorithm. Greedy algorithm is the right method to solve optimization problems, including the size of the fabric. With the method used, it is indicated that it can make it easier for producers or makers of typical clothes patterns for the Samarinda sarong woven cloth to find out the size of the woven cloth they need. Therefore, in this study several stages were carried out, including the first stage analyzing the medium-sized clothing pattern, the second stage measuring the area of each pattern on the shirt section, and the third stage installing a medium-sized pattern on the woven cloth typical of Samarinda sarong by optimizing the width of the cloth. there is. The application of the typical cloth woven sarong pattern of Samarinda by using the greedy algorithm on the medium size can be concluded to be able to optimize the use of these fabrics. This systematic stage can make it easier for producers or makers of typical Samarinda sarong woven cloth to utilize the woven fabric to the minimum so that there is no waste of the Samarinda sarong woven fabric. Keywords: Shirt, Typical fabric woven sarong Samarinda, Patterns, Greedy Algorithm